DEVELOPMENT AND USABILITY OF AN EMI-POLYZONE ON BASIC POLYGONS IN FORM ONE - Nur Amirah Amiruddin; Nurul Huda Mohamed; Nurul Akmal Mohamed; Nurul Farihan Mohamed (JP2MS, 2026)
This study aims to develop eMI-PolyZone a multimedia-based interactive learning tool focused on basic polygons for Form One students, and to evaluate its usability. The research adopts a Design Research Development (DRD) approach using ADDIE model as the development framework. The eMI-PolyZone module integrates interactive exercises and notes to support student learning. The usability of eMI-PolyZone is tested through a questionnaire administered to 30 randomly selected students from a secondary school. The instrument employed a 4-point Likert scale, and data were analyzed descriptively using SPSS Version 29. The results indicate high usability across three dimensions: perceived usefulness (mean = 3.85), ease of use (mean = 3.86), and user satisfaction (mean = 3.87). These findings suggest that the module meets usability standards and is well-received by students. In conclusion, eMI-PolyZone has the potential to create a more dynamic and engaging learning environment, thereby enhancing students’ interest and understanding of basic polygon concepts.